Oxcarbazepine monotherapy in children with benign epilepsy with centrotemporal spikes improves quality of life - Liu, Wan-Ting (Chin Med J (Engl), 2020)
BACKGROUND: Benign epilepsy with centrotemporal spikes (BECTS) is the most common type of childhood idiopathic focal epilepsy. BECTS is associated with pervasive cognitive deficits and behavior problems. While seizures can be easily controlled, it is crucial to select anti-epileptic drugs that do not impair cognition, do not cause psychosocial effects, and improve the quality of life. Previous studies showed effects of oxcarbazepine (OXC) monotherapy on the cognitive and psychosocial profiles of patients with BECTS. Here, we studied the effects of OXC monotherapy on the neuropsychologic profiles and quality of life in patients with BECTS in China. METHODS: Thirty-one patients aged 6 to 12 years newly diagnosed with BECTS were recruited. A psychometric assessment was performed before and during the follow-up of OXC monotherapy with Cognitive Computerized Task Battery, Depression Self-Rating Scale for children, Screen for Child Anxiety Related Emotional Disorders, and Quality of Life in Epilepsy-31 (QOLIE-31). The results of the assessments were compared to explore the effect of OXC monotherapy in patients with BECTS. RESULTS: Thirty children with BECTS completed the study. Five of ten cognitive test scores improved after treatment via OXC monotherapy, including visual tracing (F = 14.480, P < 0.001), paired associated learning (language) (F = 6.292, P < 0.001), paired associated learning (number) (F = 9.721, P < 0.05), word semantic (F = 6.003, P < 0.05), and simple subtraction (F = 6.229, P < 0.05). Of the neuropsychology data concerning the quality of life, statistically significant improvements were observed in emotion (F = 4.946, P < 0.05), QOLIE-social (F = 5.912, P < 0.05), and QOLIE-total (F = 14.161, P < 0.001). CONCLUSIONS: OXC is safe and does not impair neuropsychologic functions, with no obvious mood burden on children with BECTS. Most importantly, OXC has positive impacts on children's perception of quality of life, especially in terms of happiness and life satisfaction.